Two cases with avoidant/restrictive food intake disorder (ARFID): Effectiveness of EMDR and CBT combination on eating disorders (ED) - (:unkn) unknown (KLINIK PSIKIYATRI DERGISI, 2019)
Traumatic life events are among the etiological factors that may trigger eating disorders (ED). In the present study, we examined the effects of Eye Movement Desensitization and Reprocessing (EMDR) therapy and Cognitive Behavioral Therapy (CBT) therapies combined on two young girls, who had symptoms of ED as a consequence of their traumatic experiences. Two Caucasian female patients arrived at the clinic with highly similar complaints about eating. They both were mutually holding the fear that food would get stuck in their throat, breathing would be impeded and their heart rate would increase; creating an inability to swallow while eating. This culminated in a fear of death through asphyxiation while eating. In the initial interviews, the clients revealed past traumatic events in which a food blockage in the throat led to a temporary inability to breathe. Therefore, we conducted EMDR therapy combined with CBT. Both were treated with seven sessions of EMDR therapy and nine sessions of CBT, after which symptoms were reduced to minimum. In this case study, EMDR therapy combined with CBT proved to be effective by neutralizing the impact of previous trauma on ED symptomatology.
Keywords: Eating Disorders (ED); Avoidant/Restrictive Food Intake Disorder (ARFID); Eye Movement Desensitization Reprocessing (EMDR); Cognitive Behavioral Therapy (CBT); COGNITIVE-BEHAVIORAL THERAPY